2022
DOI: 10.3390/healthcare10061005
|View full text |Cite
|
Sign up to set email alerts
|

The Complexities of Prescribing Assistive Equipment at the End of Life—Patient and Caregivers’ Perspectives

Abstract: Ongoing participation in valued and essential everyday activities remains a priority for people with advanced disease. This study sought to understand factors influencing patients with advanced disease and caregivers’ utilisation of assistive equipment that enable this participation. Employing a pragmatic approach, purposive sampling identified participants who were interviewed in their homes. A semi-structured interview guide was employed to elicit community dwelling patients’ and caregivers’ perspectives abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…Recent research, outside of symptom management, has identified that adults receiving palliative care seek to maintain independence (leading to reduced carer burden and improved QOL),1–3 5 the ability to get around1 6 and engage in self-care routines 5 6. Assistive equipment may help this population perform their activities of daily living with the potential benefits of saving time and energy,4 as well as enable participation 6…”
Section: Introductionmentioning
confidence: 99%
“…Recent research, outside of symptom management, has identified that adults receiving palliative care seek to maintain independence (leading to reduced carer burden and improved QOL),1–3 5 the ability to get around1 6 and engage in self-care routines 5 6. Assistive equipment may help this population perform their activities of daily living with the potential benefits of saving time and energy,4 as well as enable participation 6…”
Section: Introductionmentioning
confidence: 99%